ABCD: Anthropometry, Body Composition, and Crohn Disease. Issue 1 (July 2016) - Brookes, Denise S.K.; Briody, Julie N.; Davies, Peter S.W.; Hill, Rebecca J.
ABSTRACT: Background: Young individuals with Crohn disease (CD) are at risk of poor bone mineral density (BMD) and reduced lean tissue mass (LTM). The importance of LTM for maintaining skeletal health, in both incident and established CD, is evidenced. We used dual-energy x-ray absorptiometry assessment to identify areal BMD and LTM in individuals with CD. Methods: In 57 patients with CD (15F; 12.99–14.16 years) anthropometric, disease activity, bone age assessment, and total body dual-energy x-ray absorptiometry measurements were acquired. A 4-step algorithm was used to assess simultaneous bone and body composition data: areal BMD and height z scores, and LTM for height and bone mineral content (BMC) for LTM z scores were calculated. Low z score cut-off values were defined as ⩽1 standard deviations below the population means. Results: The CD cohort showed: low areal BMD z scores ( P  = 0.00); and low LTM for height ( P  = 0.00) according to defined cut-off values. BMC appeared to be adapting for the lower amount of LTM. Correcting for bone age eliminated the low areal BMD z scores. As expected, LTM for height and BMC for LTM z scores remained unchanged. Conclusions: We present a useful clinical algorithm to show significant LTM for height deficits, regardless of chronological or bone age, in this CD cohort. BMC seemed to adapt to the reduced LTM, indicating clinically "normal" areal BMD for age when considered for height. The ongoing deficits in LTM may, however, create chronic long-term consequences for bone health. Improving LTM should be a focus of clinical treatment in individuals with CD.